Implications of Go-Jek Driver Fictional Order Fraud in Increasing Profits From Driver Points - Koeshardjono, R Hery; Suharsono, Judi; Ardiansyah, Edi Irgi (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2024)
The purpose of this research is to determine the effect of fraud on fictitious orders from GO-JEK drivers in increasing profits from point drivers. A case study was carried out at PT GO-JEK, Probolinggo City. The type of research used is quantitative research with an associative approach. The population chosen was GO-JEK drivers from Probolinggo City which has a population of 250 people. By taking a sample of 35 people using probability sampling techniques. The research results for the first month of the Chi-square test showed a p-value of 0.251, using an alpha of 0.05, the p-value or sig. > 0.05 or the calculated χ 2 value is 1050,000 > χ 2 table is 5.99146, meaning there is enough data to accept H1 and reject H0, so there is an effect of fraud on increasing profits. For the second month, the Chi-square test results obtained a p-value of 0.244, using an alpha of 0.05, the p-value or sig. > 0.05 or the calculated χ 2 value is 1120,000 > χ 2 table is 5.99146. Also with enough data to accept H1. This means that H0 is rejected, so there is an effect of fraud on increasing profits.